Differential effects of late gestation maternal overnutrition on the regulation of surfactant maturation in fetal and postnatal life. (24th August 2017) - Lock, Mitchell C.; McGillick, Erin V.; Orgeig, Sandra; McMillen, I. Caroline; Mühlhäusler, Beverly S.; Zhang, Song; Morrison, Janna L.
Abstract : Key points: Offspring of overweight and obese women are at greater risk for respiratory complications at birth. We determined the effect of late gestation maternal overnutrition (LGON) in sheep on surfactant maturation, glucose transport and fatty acid metabolism in the lung in fetal and postnatal life. There were significant decreases in surfactant components and numerical density of surfactant producing cells in the alveolar epithelium due to LGON in the fetal lung. However, there were no differences in the levels of these surfactant components between control and LGON lambs at 30 days of age. The reduced capacity for surfactant production in fetuses as a result of LGON may affect the transition to air breathing at birth. There was altered glucose transport and fatty acid metabolism in the lung as a result of LGON in postnatal life. However, there is a normalisation of surfactant components that suggests accelerated maturation in the lungs after birth. Abstract: With the increasing incidence of obesity worldwide, the proportion of women entering pregnancy overweight or obese has increased dramatically. The fetus of an overnourished mother experiences numerous metabolic changes that may modulate lung development and hence successful transition to air breathing at birth. We used a sheep model of maternal late gestation overnutrition (LGON; from 115 days' gestation, term 147 ± 3 days) to determine the effect of exposure to an increased plane of nutrition in late gestation on lung development in the fetus (at 141 days' gestation) and the lamb (30 days after birth). We found a decrease in the numerical density of surfactant protein positive cells, as well as a reduction in mRNA expression of surfactant proteins (SFTP‐A, ‐B and ‐C), a rate limiting enzyme in surfactant phospholipid synthesis (phosphate cytidylyltransferase 1, choline, α; PCYT1A), and glucose transporters (SLC2A1 and SLC2A4) in the fetal lung. In lambs at 30 days after birth, there were no differences between Control and LGON groups in the surfactant components that were downregulated in the LGON fetuses. However, mRNA expression of SFTP‐A, PCYT1A, peroxisome proliferator activated receptor‐γ, fatty acid synthase and fatty acid transport protein were increased in LGON lambs compared to controls. These results indicate a reduced capacity for surfactant production in late gestation. While these deficits are normalised by 30 days after birth, the lungs of LGON lambs exhibited altered glucose transport and fatty acid metabolism, which is consistent with an enhanced capacity for surfactant synthesis and restoration of surfactant maturity in these animals. Key points: Offspring of overweight and obese women are at greater risk for respiratory complications at birth. We determined the effect of late gestation maternal overnutrition (LGON) in sheep on surfactant maturation, glucose transport and fatty acid metabolism in the lung in fetal and postnatal life. There were significant decreases in surfactant components and numerical density of surfactant producing cells in the alveolar epithelium due to LGON in the fetal lung. However, there were no differences in the levels of these surfactant components between control and LGON lambs at 30 days of age. The reduced capacity for surfactant production in fetuses as a result of LGON may affect the transition to air breathing at birth. There was altered glucose transport and fatty acid metabolism in the lung as a result of LGON in postnatal life. However, there is a normalisation of surfactant components that suggests accelerated maturation in the lungs after birth.